The Aspects, the Origin, and the Merit of Aware Computing. (24th June 2012) - Sawada, Yasuji
Abstract : In this paper we tried to understand scientifically the awareness, a daily word. Some aspects of awareness, such as qualitative or quantitative, the targets of awareness, either the external world or the internal world, were discussed. Suggestion on the human awareness was described from the experimental results of visual hand tracking. The origin and the merit of awareness in the process of evolution of animals were discussed. Finally some characters of possible aware computers and aware robots were studied.